Association of Lemon Sign of Fetal Skull With Spina Bifida (Medical Forum Monthly, 2020)
Objective: To study Association of lemon sign of fetal skull with spina bifidaStudy design: Observational study.Place and Duration of Study: This study was conducted at Allama Iqbal Memorial Teaching Hospital Sialkot during Jan 2018 to Jan 2020.Materials and methods; Fifty cases of Association of lemon sign of fetal skull with spina bifida, were included in this study. Ultrasonography was conducted for all the fifty cases showing lemon sign of fetal skull to study the association of lemon sign with the spina bifida. Written informed consent of the parents was taken before collection of data. Permission of ethical committee was also considered for collection of data and publishing in medical journal.Results; Among fifty fetuses showing lemon sign of skull, forty nine showed spina bifida. Only one fetus demonstrating typical lemon shaped skull showed no evidence of spina bifida or associated abnormality. All the fetuses demonstrating spina bifida also shown associated features suggestive of Chiari malformations.Conclusion: Lemon sign shows a strong association with spina bifida and spina bifida is strongly associated with Arnold Chiari malformation.